Systems Change Analysis of Sexual Assault Nurse Examiner (SANE) Programs in One Midwestern County of the United States, 1994-2007 - Campbell, Rebecca ([Verlag nicht ermittelbar], 2011)
The purpose of this study was to determine whether adult sexual assault cases in a Midwestern community were more likely to be investigated and prosecuted after the implementation of a Sexual Assault Nurse Examiner (SANE) program, and to identify the 'critical ingredients' that contributed to that increase. Part 1 (Study 1: Case Records Quantitative Data) used a quasi-experimental, nonequivalent comparison group cohort design to compare criminal justice systems outcomes for adult sexual assault cases treated in county hospitals five years prior to the implementation of the Sexual Assault Nurse Examiner (SANE) program (January 1994 to August 1999) (the comparison group, n=156) to cases treated in the focal SANE program during its first seven years of operation (September 1999 to December 2005) (the intervention group, n=137). Variables include focus on case outcome, law enforcement agency that handled the case, DNA findings, and county-level factors, including prosecutor elections and the emergence of the focal SANE program. Part 2 (Study 2: Case Characteristics Quantitative Data) used the adult sexual assault cases from the Study 1 intervention group (post-SANE) (n=137) to examine whether victim characteristics, assault characteristics, and the presence and type of medical forensic evidence predicted case progression outcomes. Part 3 (Study 3: Police and Prosecutors Interview Qualitative Data) used in-depth interviews in April and May of 2007 with law enforcement supervisors (n=9) and prosecutors (n=6) in the focal county responsible for the prosecution of adult sexual assault crimes to explore if and how the SANEs affect the way in which police and prosecutors approach such cases. The interviews focused on four main topics: (1) whether they perceived a change in investigations and prosecution of adult sexual assault cases in post-SANE, (2) their assessment of the quality and utility of the forensic evidence provided by SANEs, (3) their perceptions regarding whether inter-agency training has improved the quality of police investigations and reports post-SANE, and (4) their perceptions regarding if and how the SANE program increased communication and collaboration among legal and medical personnel, and if such changes have influenced law enforcement investigational practices or prosecutor charging decisions.Part 4 (Study 4: Police Reports Quantitative Data) examined police reports written before and after the implementation of the SANE program to determine whether there had been substantive changes in ways sexual assaults cases were investigated since the emergence of the SANE program. Variables include whether the police had referred the case to the prosecutor, indicators of SANE involvement, and indicators of law enforcement effort. Part 5 (Study 5: Survivor Interview Qualitative Data) focused on understanding how victims characterized the care they received at the focal SANE program as well as their expriences with the criminal justices system. Using prospective sampling and community-based retrospective purposive sampling, twenty adult sexual assault vicitims were identified and interviewed between January 2006 and May 2007. Interviews covered four topics: (1) the rape itself and initial disclosures, (2) victims' experiences with SANE program staff including nurses and victim support advocates, (3) the specific role forensic evidence played in victims' decisions to participate in prosecution, and (4) victims' experiences with law enforcement, prosecutors, and judicial proceedings, and if/how the forensic nurses and advocates influenced those interactions. Part 6 (Study 6: Forensic Nurse Interview Qualitative Data) examined forensic nurses' perspectives on how the SANE program could affect survivor participation with prosecution indirectly and how the interactions between SANEs and law enforcement could be contributing to increased investigational effort. Between July and August of 2008, six Sexual Assault Nurse Examiners (SANEs) were interviewed. The interviews explored three topics: (1) the nurses' philosophy on victim reporting and participating in prosecution, (2) their perceptions regarding how patient care may or may not affect victim participation in the criminal justice system, and (3) their perception of how the SANE programs influence the work of law enforcement investigational practices.The interviews explored three topics: (1) the nurses' philosophy on victim reporting and participating in prosecution, (2) their perceptions regarding how patient care may or may not affect victim participation in the criminal justice system, and (3) their perception of how the SANE programs influence the work of law enforcement investigational practices.